Relationship between self-reported weight change, educational status, and health-related quality of life in patients with diabetes in Luxembourg - Tchicaya, Anastase (Health Qual Life Outcomes, 2015)
BACKGROUND: The aim of this study was to assess the relationship between self-reported weight change, socio-economic status, and health-related quality of life (HRQOL) in patients with diabetes, 5 years after they underwent coronary angiography. METHODS: Between 2013 and 2014, 1873 of 4391 patients (319 with diabetes) who underwent coronary angiography between 2008 and 2009 participated in a follow-up study. Three out of four domains of the World Health Organization Quality of Life (WHOQOL)-BREF (physical health, psychological health and social relationships) were surveyed during the follow-up period. To assess the relationship between weight change and HRQOL, generalized linear models were constructed for every dimension of the WHOQOL-BREF, with educational level as a predictor and sex, age, marital status, smoking status, hypertension, cholesterol, ischemic heart disease, acute myocardial infarction, and stable angina pectoris as covariates. RESULTS: The mean age of the patients was 70 years and almost three-quarters of the patients (72.7 %) were men. During the 12 months preceding the follow-up survey, 22.6 % of the patients reported weight loss, 20 % reported weight gain, and 57.4 % reported no weight change. There were significant differences in the HRQOL scores between patients who reported weight loss and those who reported either weight gain or unchanged weight. The most affected domains were physical and psychological health, with higher scores for patients who reported weight loss (54.7 and 67.2, respectively) than those who reported weight gain (46.3 and 58.5, respectively). The generalized linear model confirmed higher HRQOL scores among patients who reported weight loss and revealed an association between the HRQOL score and education level. CONCLUSION: Weight change and education level were associated with HRQOL in patients with diabetes. Self-reported weight loss and no weight change were positively associated with HRQOL in patients with diabetes, while weight gain was negatively associated with HRQOL.